Anomalous change of Airy disk with changing size of spherical particles. (February 2016) - Pan, Linchao; Zhang, Fugen; Meng, Rui; Xu, Jie; Zuo, Chenze; Ge, Baozhen
Abstract: Use of laser diffraction is considered as a method of reliable principle and mature technique in measurements of particle size distributions. It is generally accepted that for a certain relative refractive index, the size of the scattering pattern (also called Airy disk) of spherical particles monotonically decreases with increasing particle size. This fine structure forms the foundation of the laser diffraction method. Here we show that the Airy disk size of non-absorbing spherical particles becomes larger with increasing particle size in certain size ranges. To learn more about this anomalous change of Airy disk (ACAD), we present images of Airy disk and curves of Airy disk size versus particle size for spherical particles of different relative refractive indices by using Mie theory. These figures reveal that ACAD occurs periodically for non-absorbing particles and will disappear when the absorbing efficiency is higher than certain value. Then by using geometrical optics (GO) approximation, we derive the analytical formulae for the bounds of the size ranges where ACAD occurs. From the formulae, we obtain laws of ACAD as follows: (1) for non-absorbing particles, ACAD occurs periodically, and when the particle size tends to infinity, the period tends to a certain value. As the relative refractive index increases, (2) the particle size ranges where ACAD occurs shift to smaller values, (3) the period of ACAD becomes smaller, and (4) the width of the size ranges where ACAD occurs becomes narrower. In addition, we can predict from the formulae that ACAD also exists for particles whose relative refractive index is smaller than 1. Highlights: The anomalous change of Airy disk (ACAD) is presented. ACAD exists for any non-absorbing spherical particles. ACAD depends on the relative refractive index of the particles to the medium. The laws of ACAD are revealed.